ON THE USE OF MODERN APPLICATIONS IN ENGLISH CLASS - Ruiyang, Wang; Yuan, Zhou (PEOPLE: International Journal of Social Sciences, 2020)
Recently, more and more modern applications have been applied to the English learning class, among which the most outstanding ones are the ‘The Rain Classroom’ and ‘The Super Star’. The first one, ‘The Rain Classroom’ is a mini-program in Wechat, through which the students can get connected to the teacher directly; they can do homework online and express their ideas on the class’ screen simultaneously. The second one, ‘The Super Star’ is an application that the students have to download on the mobile-phone, and then they can scan the teachers’ material and assignment in the app. In this essay, in order to make a comparison between the two apps, the author tries to carry an investigation and an experiment into the students, so as to find a better way of using the modern applications, in which case, can attract the students’ attention, arouse their interest and guarantee their speaking and writing hours at the same time. Furthermore, more scholars can get a better understanding of these two apps through the essay, and the producers of the app will be able to make some adjustment to them timely. This essay will form a new viewpoint on the multimedia English teaching in China, even in the world.